Student Self-Efficacy and Readiness in Higher Education: Their Impact On Student Participation In National Academic Innovation Programs (MBKM) - Thahir, Muthahharah; Widiawati, Widiawati; Rachmaniar, Ananda; Putri, Aulia Asyifani (Universitas Ahmad Dahlan, 2025)
Background/purpose. The Merdeka Belajar Kampus Merdeka (MBKM) program is a higher education policy designed to foster student autonomy through experiential learning across campuses and industry settings. However, student participation in this program remains suboptimal, potentially influenced by internal factors such as self-efficacy and learning readiness. This study aims to examine the influence of self-efficacy and student readiness on the interest in participating in the MBKM program at Ma’soem University.Materials/methods. This research employed a quantitative approach using a survey method involving 318 active undergraduate students. The research instrument was a five-point Likert scale questionnaire, which had undergone validity and reliability testing using SPSS. Data were collected both in person and via Google Forms, following a prior explanation of the study's purpose and instructions for completion. Data analysis was conducted using multiple linear regression with the assistance of JASP software, preceded by classical assumption testing as prerequisites.Results. The results indicate that self-efficacy and student readiness jointly have a significant influence on students’ interest in participating in the MBKM program, with a coefficient of determination (R²) of 0.517, equivalent to 51.7%. The resulting regression equation is Ŷ = 4.436 + 0.487X₁ + 0.475X₂, demonstrating a positive contribution of both variables to student interest.Conclusion. Self-efficacy and learning readiness significantly affect students’ interest in participating in the MBKM program. These findings highlight the importance for higher education administrators to strengthen the development of students’ personal and academic capacities to promote active participation in the MBKM policy